PENGARUH GENDER, RISK PREFERENCES DAN PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) TERHADAP KEPUTUSAN INVESTASI - Lenita Waty; Grace Orlyn Sitompul; Francis Hutabarat (Universitas Teuku Umar, 2023)
As a result of the post-pandemic economic downturn, many people have lost a significant portion of their wealth. The right investment decision is required to get out of this mess. One way to recoup depreciating assets is through investment choices that vary depending on factors such as the investor's risk tolerance and level of digital literacy. The research in this article aims to shed light on how gender, risk aversion, and the use of ICT all play a role in financial investment choices. In this investigation, a questionnaire served as the research tool of choice. A total of 239 Indonesian professionals participated in this study. SPSS 26.0 statistics were used for this study. This study employs a variety of statistical tests and measures of correlation and independence to determine its findings. The study found that the demographic factors of gender, Risk Preferences, and the use of ICT all together significantly affect investment decisions and that the use of ICT itself partially significantly affects investment decisions.